2023
DOI: 10.1101/2023.01.06.522959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural characterization of the “totonou” state associated with sauna use

Abstract: Saunas are becoming increasingly popular worldwide, being an activity that promotes relaxation and health. Intense feelings of happiness have been reported shortly after enjoying a hot sauna and cold water, what is known in Japan as the "totonou" state. However, no research has investigated what occurs in the brain during the "totonou" state. In the present study, participants underwent a sauna phase, consisting of three sets of alternating hot sauna, cold water, and rest. We elucidated changes in brain activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Interestingly, recent studies indicate that saunas not only facilitate physical relaxation but also significantly increase alpha brain activity [7]. Moreover, our recent research [8] found increased theta and alpha waves after three sauna sessions. Moreover, in the oddball task conducted before and after, there was an increase in mismatch negativity (MMN) amplitude and a reduction in P300 amplitude after the sauna.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Interestingly, recent studies indicate that saunas not only facilitate physical relaxation but also significantly increase alpha brain activity [7]. Moreover, our recent research [8] found increased theta and alpha waves after three sauna sessions. Moreover, in the oddball task conducted before and after, there was an increase in mismatch negativity (MMN) amplitude and a reduction in P300 amplitude after the sauna.…”
Section: Introductionmentioning
confidence: 87%
“…The questionnaire survey consisted of 14 items, extracted from our previous research. These items were chosen because they showed significant changes before and after sauna bathing [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation